Fecal Microbiota Signatures in Celiac Disease Patients With Poly-Autoimmunity - Bibbò, Stefano; Abbondio, Marcello; Sau, Rosangela; Tanca, Alessandro; Pira, Giovanna; Errigo, Alessandra; Manetti, Roberto; Pes, Giovanni Mario; Dore, Maria Pina; Uzzau, Sergio (Frontiers in Cellular and Infection Microbiology, 2020)
To date, reliable tests enabling the identification of celiac disease (CD) patients at a greater risk of developing poly-autoimmune diseases are not yet available. We therefore aimed to identify non-invasive microbial biomarkers, useful to implement diagnosis of poly-autoimmunity. Twenty CD patients with poly-autoimmunity (cases) and 30 matched subjects affected exclusively by CD (controls) were selected. All patients followed a varied gluten-free diet for at least 1 year. Fecal microbiota composition was characterized using bacterial 16S ribosomal RNA gene sequencing. Significant differences in gut microbiota composition between CD patients with and without poly-autoimmune disease were found using the edgeR algorithm. Spearman correlations between gut microbiota and clinical, demographic, and anthropometric data were also examined. A significant reduction of Bacteroides, Ruminococcus, and Veillonella abundances was found in CD patients with poly-autoimmunity compared to the controls. Bifidobacterium was specifically reduced in CD patients with Hashimoto's thyroiditis and its abundance correlated negatively with abdominal circumference values in patients affected exclusively by CD. In addition, the duration of CD correlated with the abundance of Firmicutes (negatively) and Odoribacter (positively), whereas the abundance of Desulfovibrionaceae positively correlated with the duration of poly-autoimmunity. This study provides supportive evidence that specific variations of gut microbial taxa occur in CD patients with poly-autoimmune diseases. These findings open the way to future validation studies on larger cohorts, which might in turn lead to promising diagnostic applications.